Evaluation of atmospheric indicators in the Adriatic coastal areas: a multi-hazards approach for a better awareness of the current and future climate - Fedele, Giusy; Manco, Ilenia; Barbato, Giuliana; Verri, Giorgia; Mercogliano, Paola (Frontiers in Climate, 2024)
Increasing the climate resilience to global warming is one of the main challenges of the last decades. Effective local measures have to be adopted for providing concrete solutions to current and expected impacts of climate change. This is the goal of the AdriaClim Italia-Croatia Interreg Project (https://www.italy-croatia.eu/web/adriaclim), aimed at supporting the development of regional and local climate change adaptation plans on the Adriatic coastal regions. For this purpose, an exhaustive number of atmospheric climate indicators has been identified and evaluated over 9-pilot areas in order to assess the current and expected main climate hazards hitting these regions, considering the worst-case emissions scenario (Representative Concentration Pathway RCP 8.5). The proposed analyses are provided by the results of the regional climate atmospheric model developed within the AdriaClim Project. The selected climate indicators are used to assess the possible evolution of the climate hazard over the pilot areas, covering different hazards, such as thermal discomfort, drought and hydrological instability. A site-dependent investigation of the atmospheric climate indicators is proposed to emphasize which regions are more affected than others by the investigated climate hazards, and therefore deserve more attention in defining and proposing new adaptation strategies. Results highlight increasing temperatures (up to +3 degree C) over the Adriatic coastal regions, more emphasized in the Northern Adriatic, where the joint effect with the relevant decrease in precipitation (down to -2 mm/day), may lead to severe drought conditions in the next decades. In contrast, precipitation-related diseases may hit more Central and South Italy then the Northern Adriatic, except for the Emilia Romagna region, which is found to be highly sensitive to both the hazard categories. Finally, it is relevant to emphasize that these analyses have to be carefully considered on supporting adaptation strategies due to the lack of uncertainty estimates representing a fundamental element for decision makers.